2012
DOI: 10.1159/000334400
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Surface Marker Expression and Chondrogenic Potential among Various Tissue-Derived Mesenchymal Cells from Elderly Patients with Osteoarthritis

Abstract: Mesenchymal stem cells (MSCs) are self-renewing, multipotent cells that could potentially be used to repair injured cartilage in diseases such as osteoarthritis (OA). In this study we used bone marrow, adipose tissue from articular and subcutaneous locations, and synovial fluid samples from 18 patients with knee OA to find a suitable alternative source for the isolation of MSCs with high chondrogenic potential. MSCs from all tissues analysed had a fibroblastic morphology, but their rates of proliferation varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 119 publications
4
21
0
Order By: Relevance
“…Therefore, insights into the multipotency and efficiency of differentiation into different lineages of MSCs from IFP of OA versus healthy individuals are lacking. Comparison between MSCs from IFP, sc adipose tissue, bone marrow, and synovial fluid of patients with OA has indicated that IFP MSCs are most similar in phenotype (that is, surface marker expression) to sc adipose tissue MSCs but have proliferative and chondrogenic differentiation capacities most similar to bone marrow MSCs [54]. However, in a different study, IFP MSCs displayed enhanced chondrogenic and adipogenic capacity when compared with normal bone marrow MSCs [55], although differences in age between the OA and healthy population could account for this difference.…”
Section: Infrapatellar Fat Pad As a Source Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Therefore, insights into the multipotency and efficiency of differentiation into different lineages of MSCs from IFP of OA versus healthy individuals are lacking. Comparison between MSCs from IFP, sc adipose tissue, bone marrow, and synovial fluid of patients with OA has indicated that IFP MSCs are most similar in phenotype (that is, surface marker expression) to sc adipose tissue MSCs but have proliferative and chondrogenic differentiation capacities most similar to bone marrow MSCs [54]. However, in a different study, IFP MSCs displayed enhanced chondrogenic and adipogenic capacity when compared with normal bone marrow MSCs [55], although differences in age between the OA and healthy population could account for this difference.…”
Section: Infrapatellar Fat Pad As a Source Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…MSCs isolated from human umbilical cord Wharton's jelly by the collagenase/trypsin method are enriched in expression of C-kit and Oct-4 [53]. MSCs from bone marrow and Hoff's fat pad show a high potential to differentiate into chondrocytes whereas MSCs from subcutaneous fat demonstrate a poor potential for chondrogenesis [54]. Rabbit and sheep MSCs were able to differentiate into chondrocytic lineages much more easily than human MSCs [45].…”
Section: Phenotypically and Functionally Heterogeneous Mscsmentioning
confidence: 99%
“…The proliferative and differentiation capacities of synovial fluidderived progenitor cells have varied between studies [9][10][11][12][13], but in all cases, these cells were capable of chondrogenesis. However, the specific chondrogenic lineage of synovial fluidderived chondroprogenitors (SF-CP) has not been defined.…”
Section: Introductionmentioning
confidence: 99%